Robin Huws Jones (United Kingdom), President 1976- 1980 - Katherine A. Kendall (Social Work and Society, 2008)
Robin Huws Jones, President of the International Association of Schools of Social Work from 1976 to 1980, lived a life of challenge and change. Born in Wales in 1909, he often remarked that learning to speak Welsh at age two was such a challenge that he didn't bother to learn English until he was six. The death of his mother when he was three led to the first of many changes in a life that was not easy in the formative years. Robin remained in the care of his father while his sister became the ward of two aunts. With his father, a draper'sassistant, he left Wales to live in a crowded boarding house in Liverpool.